Framework development of real-time lip sync Animation on viseme based human speech - Loh, Ngiik Hoon; Khairul Aidil Azlin, Abd. Rahman; Wang, Yin Chai (UTM Press, 2015)
Performance of real-time lip sync animation is an approach to perform a virtual computer generated character talk, which synchronizes an accurate lip movement and sound in live. Based on the review, the creation of lip sync animation in real-time is particularly challenging in mapping the lip animation movement and sounds that are synchronized. The fluidity and accuracy in natural speech are one of the most difficult things to do convincingly in facial animation. People are very sensitive to this when you get it wrong because we are all focused on faces. Especially in real time application, the visual impact needed is immediate, commanding and convincing to the audience. A research on viseme based human speech was conducted to develop a lip synchronization platform in order to achieve an accurate lip motion with the sounds that are synchronized as well as increase the visual performance of the facial animation. Through this research, a usability automated digital speech system for lip sync animation was developed. Automatic designed with the use of simple synchronization tricks which generally improve accuracy and realistic visual impression and implementation of advanced features into lip synchronization application. This study allows simulation of lip synching in real time and offline application. Hence, it can be applied in various areas such as entertainment, education, tutoring, animation and live performances, such as theater, broadcasting, education and live presentation.